The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.17957/tpmj/17.3635
|View full text |Cite
|
Sign up to set email alerts
|

Cirrhotic Patients; Frequency and Pattern of Gastric Vascular Changes

Abstract: At present time portal hypertension is perceived as one of the complications of advanced liver disease. It results in various vascular changes in gastrointestinal tract (GI), including esophageal varices, gastric varices and portal hypertensive gastropathy (PHG). PHG and gastric varices are a common cause of acute as well as chronic bleeding from GI tract which resulted in significant mortality among patients. Objectives: To determine the frequency of gastric vascular changes in various causes of cirrhosis. Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
(6 reference statements)
0
1
0
Order By: Relevance
“…[13][14][15] Our study has demonstrated that as liver dysfunction progresses to higher child Pugh's Class (Class-C),the tendency of varices formation & bleeding also rises; similar observations have been documented by previous studies. 16,17 It was found that liver dysfunction and complications of liver cirrhosis (Child-Pugh Class-B 82%, Child-Pugh Class C 87%) were more common in middle age and elderly patients between 40-80 years. This group of patients was more commonly seen in the Emergency Department with hematemesis, which may mean that older age is associated with higher Child Pugh's Class and formation of large oesophagal varices and increased bleeding tendency, where this may be due to the chronicity of disease itself.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15] Our study has demonstrated that as liver dysfunction progresses to higher child Pugh's Class (Class-C),the tendency of varices formation & bleeding also rises; similar observations have been documented by previous studies. 16,17 It was found that liver dysfunction and complications of liver cirrhosis (Child-Pugh Class-B 82%, Child-Pugh Class C 87%) were more common in middle age and elderly patients between 40-80 years. This group of patients was more commonly seen in the Emergency Department with hematemesis, which may mean that older age is associated with higher Child Pugh's Class and formation of large oesophagal varices and increased bleeding tendency, where this may be due to the chronicity of disease itself.…”
Section: Discussionmentioning
confidence: 99%